Pengaruh Green Accounting dan Kinerja Lingkungan Terhadap Profitabilitas: Tinjauan Literatur Sistematis - Anggraini, Fida; Tjandrakirana DP, Rina (Journal of Economics and Business Research (JUEBIR), 2025)
This study aims to provide a deeper analysis of the effect of green accounting and environmental performance on profitability, especially for companies engaged in the oil and gas sector. The research method used in this study is systematic literature observation with the Preferred Reporting Items for Systematic Review and Meta Analyses (PRISMA) approach. Research data from articles collected from 500 articles sourced from the Harzing's Publish or Perish application using Google Scholar sources, then filtered into 27 relevant articles. The results of the study showed 5 articles stating that green accounting and environmental performance had a positive effect and 9 articles were also found discussing only one variable with a positive effect, 5 articles on green accounting variables and 4 articles on environmental performance variables. In general, these results explain that entities that apply the concept of green accounting and have environmental performance as much as 51% of the research data tend to increase long-term profitability. This is due to increased trust from stakeholders and compliance with applicable environmental regulations. However, the study also found that green accounting and environmental performance research still faces various challenges as evidenced by the weakness of the research